1999
DOI: 10.1084/jem.189.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Nature and Cellular Distribution of the Paired Immunoglobulin-like Receptors, PIR-A and PIR-B

Abstract: PIR-A and PIR-B, paired immunoglobulin-like receptors encoded, respectively, by multiple Pira genes and a single Pirb gene in mice, are relatives of the human natural killer (NK) and Fc receptors. Monoclonal and polyclonal antibodies produced against a recombinant PIR protein identified cell surface glycoproteins of ∼85 and ∼120 kD on B cells, granulocytes, and macrophages. A disulfide-linked homodimer associated with the cell surface PIR molecules was identified as the Fc receptor common γ (FcRγc) chain. Wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
2
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(159 citation statements)
references
References 50 publications
2
154
2
1
Order By: Relevance
“…16,19,26 In agreement with this findings, blocking of CD300a and PS interactions induces increased inflammatory cytokine production from mast cells, 26 and CD300f deficiency leads to a predispostion to autoimmune disease development, 19 as well as an exacerbation in the allergic responses and autoimmune diseases. 19,25,33,34 In contrast, our data characterize CD300b as a positive regulator of phagocytosis, through its association with DAP12. The exact role of CD300b in efferocytosis remains to be elucidated, but the existing data suggest that CD300b is involved in the regulation of some immune responses.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…16,19,26 In agreement with this findings, blocking of CD300a and PS interactions induces increased inflammatory cytokine production from mast cells, 26 and CD300f deficiency leads to a predispostion to autoimmune disease development, 19 as well as an exacerbation in the allergic responses and autoimmune diseases. 19,25,33,34 In contrast, our data characterize CD300b as a positive regulator of phagocytosis, through its association with DAP12. The exact role of CD300b in efferocytosis remains to be elucidated, but the existing data suggest that CD300b is involved in the regulation of some immune responses.…”
Section: Resultscontrasting
confidence: 70%
“…[29][30][31][32] Many of these balancing signals originate from activating and inhibitory receptors of closely related family members that have identical or very similar ligand specificities, for example, NKG2A and NKG2C, 29 killer-cell immunoglobulin-like receptors, 31 CD28 and CTLA4, PIR-A and PIR-B. 33 The CD300 receptors are another such family expressed mainly on myeloid cells. Furthermore, work from us and others showed that at least three members of this family, CD300a, 16,26 CD300f, 18,19 and now CD300b, recognize PS and positively or negatively regulate the phagocytosis of apoptotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…2), we call these PIR-A1, PIR-A2, PIR-A2 homologue 1 (PIR-A2h1), and PIR-A2 homologue 2 (PIR-A2h2). Association of PIR-A with FcR␥ chain is required for efficient expression of PIR-A on the surface of cells such as the LTK fibroblast cell line, macrophages, and splenocytes (33). In contrast, PIR-A presents on the surface of COS7 cells even in absence of FcR␥ (34).…”
Section: Recognition Of S Aureus By Pir Through the Ig-like Domain D2mentioning
confidence: 99%
“…We sequenced the retrovirus inserts and found that all three clones harbor PIR-B cDNA in the sense orientation. Based on cell surface staining by anti-PIR mAb 6C1 (33), parental NIH3T3 cells lacked PIR-B expression, whereas 4S2C37, 4S2C43, and 4S2C46 cells expressed PIR-B on their cell surface (Fig. 1B and data not shown).…”
Section: Identification Of Pir-b As a Receptor For S Aureusmentioning
confidence: 99%
“…PIRs are members of the Ig-superfamily characterized by six extracellular Ig-SF domains and by differing transmembrane and cytoplasmic domains. Only one PIR isotype (PIRB) is inhibitory, whereas several PIR isotypes (PIRAs) are activating [34][35][36][37]. Gp49 receptors are characterized by two Ig-SF domains and include one inhibitory and one activating isotype [29][30][31][32][33].…”
Section: Ilt Receptor Structurementioning
confidence: 99%